REACTIVE OXYGEN AND NITROGEN SPECIES ROLE IN EXPERIMENTAL PERIODONTITIS DEVELOPMENT - Demkovych, A. Ye. (International Journal of Medicine and Medical Research, 2018)
Introduction. Activation of lipid peroxidation is one of the trigger mechanisms of periodontium injury, which is primary caused by cellular damage. Reactive oxygen and nitrogen species (RONS) are able to cause damage to a cell as well as final products of lipid peroxidation, including unsaturated aldehydes and other metabolites. Objective. The aim of the research was to determine the role of RONS and accumulation of lipid peroxidation derivatives in initial development and formation of chronical inflammatory process in periodontium. Methods. Experimental periodontitis was modeled in animals by injection of complex mixtures of microorganisms diluted in egg protein into periodontal tissues. The results of biochemical studies of free radical processes activity in blood serum were evaluated by content of diene, triene conjugates, TBA-active products and total quantity of metabolites of nitric oxide (NO2–+NO3–), which were determined on the 7th, 14th and 30th days of the experiment. Results. Generation of active forms of oxygen is more influential, providing longevity of inflammatory process. This pays attention to typical dynamics of changes in active processes of lipid peroxidation in the development and course of experimental periodontitis. The study of inflammatory process with a bacterial-immune component in the rats’ periodontal complex proved accumulation of lipid peroxidation and nitric oxide metabolites in blood serum. Conclusions. The preservation of increased lipid peroxidation and nitric oxide metabolites in blood serum of the experimental animals with acute periodontitis conduce enhance of alteration and delayed healing that result in its sequel into chronical periodontitis.